Appropriate Age for Height Control Treatment in Patients With Marfan Syndrome - Kim, Sung Eun; Lee, Dong-Yun; Kim, Min-Sun; Cho, Sung Yoon; Jin, Dong-Kyu; Choi, DooSeok (Frontiers in Endocrinology, 2021)
This study aimed to determine the most appropriate age for height control treatment in patients with Marfan syndrome (MFS). This retrospective study included patients with MFS who underwent height control treatment with estradiol valerate. The estrogen dose was increased according to the height change. The cut-off age for the maximum difference between the expected height and actual final height was evaluated. Seventeen patients were included in this study. The difference between the height predicted by the growth curve and the final height (gcHtD) and that predicted by the bone age and the final height (baHtD) was the largest in the 10.5 years age group (p=0.0045 and p=0.0237, respectively). The gcHtD was 10.6 (10.2, 13.5) cm for patients aged ≤10.5 years, whereas it was 0.6 (−3.65, 5.85) cm for patients aged >10.5 years. The baHtD was 10.1 (7.31, 11.42) cm for patients aged ≤10.5 years, while it was 3.83 (0.84, 6.4) cm for patients aged >10.5 years. When height change was observed for a minimum of 6 months after completion of estrogen treatment, the average growth was 0.6 (0.2, 2.1) cm. Initiating height control treatment before the age of 10.5 years is effective in female patients with MFS.